Analysis of Canteen Selection for Bunga Bangsa Cirebon Students Using the Weighted Product (WP) Method - Jannah, Raodatul; Rahayu, Riska (Ridwan Institute, 2023)
With the rising number of canteens in Cirebon, students face a more intricate decision-making process in selecting the most suitable option. This research introduces a Decision Support System (DSS) aimed at aiding Cirebon students in effectively choosing a canteen. Utilizing the Weighted Product Method, various criteria, including distance, menu prices, parking area, atmosphere, and wifi speed, are assessed. Data collection involves observations and interviews. The system development employs technology, particularly a user-friendly application developed in collaboration with Microsoft Excel. The application provides a quantitative assessment of cafes, ranking them based on overall suitability to student preferences. This research significantly contributes to enhancing the decision-making process for students seeking an optimal canteen experience in Cirebon. The study not only offers insights into the criteria considered but also provides specific details on the outcomes derived from the Weighted Product Method. This research serves as a practical tool, allowing users to explore available canteen options with the ultimate goal of facilitating a more informed and satisfying selection process. The clear structure and refined language enhance the overall readability of the abstract.